Prevalence of metabolic syndrome with different serum vitamin D levels in middle-aged and older adults - Ya Zhao; Danting Su; Lichun Huang; Mengjie He; Dan Han; Dong Zhao; Yan Zou; Ronghua Zhang (Nutrition & Metabolism)
Abstract Background The relationship between serum vitamin D levels and metabolic syndrome (MetS) has been controversial. This study focused on the relationship between the prevalence of MetS and serum vitamin D levels in middle-aged and elderly people. Methods This study included middle-aged and older adults who participated in the 2023 Zhejiang Provincial Nutrition and Health Survey, which was conducted in 90 districts and counties in Zhejiang Province, China. Results A total of 11,305 participants were included in this study. MetS was prevalent in 31.7% of participants. Vitamin D and vitamin D3 concentrations were inversely associated with MetS prevalence (P trend<0.05), but not with vitamin D2, regardless of whether logistic regression models were adjusted for confounding factors. After adjusting for age, sex, physical activity level, smoking status, education level, annual per capita household income, and body mass index residuals, the highest tertile (Q3) of vitamin D (odds ratio [OR], 0.779; 95% confidence interval [CI], 0.702–0.865) and vitamin D3 (OR, 0.787; 95% CI, 0.709–0.875) concentrations had a lower risk of MetS than the lowest tertile (Q1). We found that vitamin D and D3 levels were correlated with age (P interaction<0.05). When age-stratified analyses were performed, vitamin D and vitamin D3 levels were significantly negatively associated with MetS in older adults but not in middle-aged adults. Conclusions Low total serum vitamin D and vitamin D3 levels were associated with a higher risk of MetS in adults aged 60 years and older.